2011
DOI: 10.1088/0004-6256/142/2/37
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Star Formation Law in the Atomic-Gas-Dominated Regime in Nearby Galaxies

Abstract: We use the IRAM HERACLES survey to study CO emission from 33 nearby spiral galaxies down to very low intensities. Using 21 cm line atomic hydrogen (H i) data, mostly from THINGS, we predict the local mean CO velocity based on the mean H i velocity. By re-normalizing the CO velocity axis so that zero corresponds to the local mean H i velocity we are able to stack spectra coherently over large regions. This enables us to measure CO intensities with high significance as low as, an improvement of about one order o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
483
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(530 citation statements)
references
References 71 publications
43
483
3
1
Order By: Relevance
“…These authors found that the SFR is principally correlated with H 2 gas (as traced by CO (J=2-1) in this case), and unassociated with HI in nearby galaxies. This result was extended to the atomic gas-dominated outskirts of nearby galaxies by Schruba et al (2011). A principle result from these groups is that the SFR is linearly related to the molecular gas surface density on resolved (a few hundred pc) scales, when assuming a constant line ratio from CO (J=2-1) to (J=1-0) (with Σ SFR ), as well as a constant X CO .…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 82%
“…These authors found that the SFR is principally correlated with H 2 gas (as traced by CO (J=2-1) in this case), and unassociated with HI in nearby galaxies. This result was extended to the atomic gas-dominated outskirts of nearby galaxies by Schruba et al (2011). A principle result from these groups is that the SFR is linearly related to the molecular gas surface density on resolved (a few hundred pc) scales, when assuming a constant line ratio from CO (J=2-1) to (J=1-0) (with Σ SFR ), as well as a constant X CO .…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 82%
“…The molecular gas phase is thought to immediately preceed star formation (e.g. , Schruba et al 2011) and this phase is thus most relevant to study a galaxy's potential to form new stars. The other phases of the ISM cannot form stars directly (but see, e.g., Glover & Clark 2012), unless they cool sufficiently to form cold and dense molecular gas.…”
Section: Galaxy Formation and The Need For Cool Gas Observationsmentioning
confidence: 99%
“…Green pixels are the data of Bolatto et al (2011) for the SMC, but with each pixel representing a 12 pc aperture; green squares and circles are the same data set, but averaged over 200 pc and 1 kpc apertures instead. Red points are averages over azimuthal rings, with widths from 220 − 1800 pc depending on the distance of the target, in nearby spiral galaxies from Schruba et al (2011). The size of the symbol indicates whether Schruba et al classify the detection as strong or marginal.…”
Section: Observational Phenomenologymentioning
confidence: 99%